1990
DOI: 10.1111/j.1476-5381.1990.tb14674.x
|View full text |Cite
|
Sign up to set email alerts
|

κ‐Opioid‐receptor agonists modulate the renal excretion of water and electrolytes in anaesthetized rats

Abstract: 1 Subcutaneous injection of the K-opioid agonists U50,488 (10mgkg-') and tifluadom (3.5mgkg-1) into Inactin-anaesthetized, saline-infused rats was associated with a diuresis, antinatriuresis and antikaliuresis which lasted for up to 2h. A high (5mgkg-1), but not low (0.1mgkg-1), dose of naloxone blocked the renal effects of U50,488. 2 U50,488 administration in anaesthetized, vasopressin-deficient Brattleboro DI rats was associated with an attenuated diuresis, though the antinatriuretic response remained intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…U-50488H has been shown to have no effect on renal plasma flow or glomerular filtration rate in the dog (Slizgi et al, 1984) and its diuretic action in the spontaneously hypertensive rat was not through an increase in the efferent renal sympathetic nerve activity (Kapusta etal., 1989). On the contrary, U-50488H has been shown to increase glomerular filtration rate while fractional fluid reabsorption remained steady in anaesthetized rat (Ashton et al, 1990) and increase plasma corticosterone levels in conscious rat (Ashton et al, 1989), hence the increase in glomerular filtration rate may be mediated through an increase in angiotensin II levels and the action of the plasma corticosterone. In our study spiradoline did not have any significant effect on either pulsatility index or peak flow velocity in the renal artery implying that renal haemodynamic changes are unlikely to account for the diuresis observed.…”
Section: Discussionmentioning
confidence: 88%
“…U-50488H has been shown to have no effect on renal plasma flow or glomerular filtration rate in the dog (Slizgi et al, 1984) and its diuretic action in the spontaneously hypertensive rat was not through an increase in the efferent renal sympathetic nerve activity (Kapusta etal., 1989). On the contrary, U-50488H has been shown to increase glomerular filtration rate while fractional fluid reabsorption remained steady in anaesthetized rat (Ashton et al, 1990) and increase plasma corticosterone levels in conscious rat (Ashton et al, 1989), hence the increase in glomerular filtration rate may be mediated through an increase in angiotensin II levels and the action of the plasma corticosterone. In our study spiradoline did not have any significant effect on either pulsatility index or peak flow velocity in the renal artery implying that renal haemodynamic changes are unlikely to account for the diuresis observed.…”
Section: Discussionmentioning
confidence: 88%
“…: Knepel et al 1982). This fact also indicates that the effect of nalox¬ one may be mediated by receptors, since high doses of naloxone are required to antagonize the action of dynorphin at the receptor and the diuretic action of U50 488H (Leander, 1983;Ashton et al 1990). Although the diuretic action of peripherally adminis¬ tered U50 488H is not associated with a change in plasma AVP concentration and can be abolished by adrenal demedulation (Ashton et al 1989), we have previously reported that U50 488H also has a prolonged central inhibitory effect on basal AVP secretion (Forsling & Wells, 1989).…”
Section: Discussionmentioning
confidence: 95%
“…administration of the selec¬ tive receptor agonist morphine has been shown to cause a long latency decrease in the plasma concen¬ tration of AVP (Van Wimersma Greidanus, Thody, Verspaget et al 1979;Aziz, Forsling & Woolf, 1981), consistent with its inhibitory influence on the phasic activity of vasopressinergic magnocellular neurones (Clarke, Lincoln & Wood, 1980;Muehlethaler, Gaehwiler & Dreifuss, 1980). Peripheral adminis¬ tration of the selective -opioid agonist U50 488H increases urine flow (Leander, 1983;Ashton, Balment & Blackburn, 1990) with no associated change in plasma AVP concentration (Ashton, Balment & Blackburn, 1989). However, it is not clear whether U50 488H has a central action to modulate AVP secretion.…”
Section: Introductionmentioning
confidence: 93%
“…The diuretic effect of -opioidreceptor activation appears to result from a combination of 1) its direct inhibitory effects on the tubular action of arginine vasopressin (AVP) in promoting water reabsorption and 2) suppression of AVP release from the neurohypophysis (2-4, 9, 25-26, 46). Despite the diuretic response to activation of -opioid receptors by either receptor agonists or the naturally occurring ligand, dynorphin A, there appears to be no consistent accompanying increase in electrolyte excretion (1)(2)48). For this reason, -opioid peptides are considered aquaretic.…”
mentioning
confidence: 92%